2023
DOI: 10.37496/rbz5220220023
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of digestible methionine + cystine for growing Japanese quail and its subsequent effects on laying phase

Abstract: The objective of this study was to estimate the nutritional requirement of digestible methionine + cystine for Japanese quail during the growth phase and its residual effect on the laying phase. One experiment was conducted, including three phases: starter, from 1 to 14 days of age; grower, from 15 to 42 days of age; and laying, from 43 to 168 days of age. The experimental design was entirely randomized with five treatments (0.52, 0.64, 0.76, 0.88, and 1.00% of digestible methionine + cystine) and five replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Shrivastav and Panda (1986) found that the maximum value of body weight gain was achieved in Japanese quail with 0.75% total sulfur amino acid during 0-6 weeks of age. Perine et al (2023) found that in the quail chick throughout 42 days of age, no significant effects (P>0.05) regarding (0.52, 0.64, 0.76, 0.88, and 1.00% of digestible methionine + cystine) levels were observed for live body weight.…”
Section: Live Body Weightmentioning
confidence: 75%
“…Shrivastav and Panda (1986) found that the maximum value of body weight gain was achieved in Japanese quail with 0.75% total sulfur amino acid during 0-6 weeks of age. Perine et al (2023) found that in the quail chick throughout 42 days of age, no significant effects (P>0.05) regarding (0.52, 0.64, 0.76, 0.88, and 1.00% of digestible methionine + cystine) levels were observed for live body weight.…”
Section: Live Body Weightmentioning
confidence: 75%